2011
DOI: 10.2139/ssrn.1965660
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Likelihood for Markov-Switching and Change-Point GARCH Models

Abstract: CIRANOLe CIRANO est un organisme sans but lucratif constitué en vertu de la Loi des compagnies du Québec. Le financement de son infrastructure et de ses activités de recherche provient des cotisations de ses organisations-membres, d'une subvention d'infrastructure du Ministère du Développement économique et régional et de la Recherche, de même que des subventions et mandats obtenus par ses équipes de recherche.CIRANO is a private non-profit organization incorporated under the Québec Companies Act. Its infrastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…We are aware that univariate GARCH and Markov-Switching models have been estimated in a single step(Bauwens et al, 2014;Augustyniak, 2014;Marcucci, 2005) Pelletier (2006). has offered an example of a DCC-GARCH with Markov-Switching.5 The Euro was launched on 1 January 1999 and replaced by 2002 the national currencies.…”
mentioning
confidence: 99%
“…We are aware that univariate GARCH and Markov-Switching models have been estimated in a single step(Bauwens et al, 2014;Augustyniak, 2014;Marcucci, 2005) Pelletier (2006). has offered an example of a DCC-GARCH with Markov-Switching.5 The Euro was launched on 1 January 1999 and replaced by 2002 the national currencies.…”
mentioning
confidence: 99%
“…The first Equation (20) refers to the DiffeRential Evolution Adaptive Metropolis (DREAM) proposal distribution of [18] and is the MCMC analog of the DE mutation (17). In their paper, it is shown that the proposal distribution is symmetric and so that the acceptance ratio is independent of the proposal density.…”
Section: Choice Of Mcmc Kernelsmentioning
confidence: 99%
“…Compared to other competitive volatility models such as Markov Switching GARCH models (Haas, Mittnik and Paolella, 2004;Francq and Zakoïan, 2008;Bauwens, Dufays and Rombouts, 2014), the AP-GARCH specification has a simpler probability structure and it is easier to estimate by maximum likelihood-type methods, a fact that makes it quite popular. However, a serious deficiency of the AP-GARCH model is that it assumes time-invariant parameters.…”
Section: Introductionmentioning
confidence: 99%